2020
DOI: 10.3390/ijerph17176339
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Malaria Transmission Dynamics in Dangassa, Mali: A Novel Approach Using Functional Generalized Additive Models

Abstract: Mali aims to reach the pre-elimination stage of malaria by the next decade. This study used functional regression models to predict the incidence of malaria as a function of past meteorological patterns to better prevent and to act proactively against impending malaria outbreaks. All data were collected over a five-year period (2012–2017) from 1400 persons who sought treatment at Dangassa’s community health center. Rainfall, temperature, humidity, and wind speed variables were collected. Functional Generalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…36,37 The WA-ICEMR studies also described seasonal spatiotemporal clusters in the distribution of P. falciparum infection and diseases that may provide opportunities for new control strategies such as reactive, community-based, self-administered treatments against residual malaria transmission or targeted vector control strategies such as larval control of vector breeding and during the dry season. 26,38 These studies also showed that spatial analyses and cluster detection approaches have considerable utility for guiding targeted intervention strategies.…”
Section: Significance Of Research Findings For Improving Malaria Cont...mentioning
confidence: 97%
“…36,37 The WA-ICEMR studies also described seasonal spatiotemporal clusters in the distribution of P. falciparum infection and diseases that may provide opportunities for new control strategies such as reactive, community-based, self-administered treatments against residual malaria transmission or targeted vector control strategies such as larval control of vector breeding and during the dry season. 26,38 These studies also showed that spatial analyses and cluster detection approaches have considerable utility for guiding targeted intervention strategies.…”
Section: Significance Of Research Findings For Improving Malaria Cont...mentioning
confidence: 97%
“…During the past decade, Mali and most SSA countries started the progressive implementation of proven malaria prevention and control strategies, such as the distribution of insecticide-treated bed nets (ITNs), indoor residual spraying (IRS) in targeted geographic areas, improved access to healthcare with early diagnosis and prompt treatment, prevention and rapid management of malaria epidemics and surveillance, provision of intermittent preventive therapy to pregnant women (IPTp), and seasonal malaria chemoprevention (SMC) for children under 5 years old. The Malian Government and its partners have been offering free malaria diagnostics and treatment to children under 5 years old and pregnant women since 2008 [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generalized Additive Models (GAMs) are commonly used to set a predictive model for infectious diseases ( Hart et al., 2009 ; Gu et al., 2015 ; Ateba et al., 2020 ). Lin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Generalized Additive Models (GAMs) are commonly used to set a predictive model for infectious diseases (Hart et al, 2009;Gu et al, 2015;Ateba et al, 2020). Lin et al (2016) used GAMs to assess the effectiveness of a community-based integrated intervention of dengue in Guangzhou and acheived significant effects to control outbreak in areas.…”
Section: Introductionmentioning
confidence: 99%